The national workshop on project cycle management, Kano, September 1988 : a report - Adeyemo, O. A.; National Centre for Economic Management and Administration (Nigeria) (Ibadan : National Centre for Economic Management and Administration, 1988)
This is a report on project cycle management organised by the National Centre for Economic Management and Administration (NCEMA) in Kano for public sector functionaries on level 15 and above. It is a summary of the outcome of workshop.
At head of title: National Centre for Economic Management and Administration (NCEMA).
lje 12/4/19
Arch.
Keywords: Economic development projects; Government spending policy; Nigeria